The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00262-012-1262-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-rate freezer cryopreservation of highly concentrated peripheral blood mononuclear cells results in higher cell yields and superior autologous T-cell stimulation for dendritic cell-based immunotherapy

Abstract: Availability of large quantities of functionally effective dendritic cells (DC) represents one of the major challenges for immunotherapeutic trials against infectious or malignant diseases. Low numbers or insufficient T-cell activation of DC may result in premature termination of treatment and unsatisfying immune responses in clinical trials. Based on the notion that cryopreservation of monocytes is superior to cryopreservation of immature or mature DC in terms of resulting DC quantity and immuno-stimulatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…The progressive rate freezing program may be critical for sensitive cell types: use of a controlled rate freezer leads to higher yields of dendritic cells and to higher autologous T cell stimulation [67] than freezing with isopropanol. The long-term storage time and temperature of the frozen cells is another critical factor.…”
Section: Cryopreservationmentioning
confidence: 99%
“…The progressive rate freezing program may be critical for sensitive cell types: use of a controlled rate freezer leads to higher yields of dendritic cells and to higher autologous T cell stimulation [67] than freezing with isopropanol. The long-term storage time and temperature of the frozen cells is another critical factor.…”
Section: Cryopreservationmentioning
confidence: 99%
“…Buhl et al compared CRF freezing with standard isopropyl alcohol freezing for downstream dendritic cell applications. 32 They showed that while similar dendritic cell viability was seen with the two methods, induction of antigen-specific IFN-g release from autologous effector T cells was significantly higher with CRF. In our study, the two freezing methods, Mr. Frosty and Controlled Rate Freezer, gave largely similar cell recovery, viability, cell subpopulation distribution, and susceptibility to EBV immortalization.…”
Section: Validation Of Pbmc Isolationmentioning
confidence: 94%
“…The Melan‐A‐TAT fusion peptide [CELAGIGILTVRKKRRQRRR, Melan‐A sequence underlined] was synthesized using standard fluorenylmethoxycarbonyl (Fmoc) chemistry. The N‐terminal Cys residue was added to enable coupling of Alexa Fluor 488 (Alexa488) C 5 maleimide (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%